Comparison of the Changes of D-Dimer and FDP Serum Levels in Ischemic Brain stroke Patients with and without Malignancy - Mohammad Reza Amiri-Nikpour (Journal of Global Pharma Technology, 2017)
Introduction: Cerebral artery diseases are the third cause of death in the U.S. proceeded only by the heart diseases and cancer. It is the most prevalent neurological disorder leading to illness and death. Stroke is a syndrome characterized by the initiation of acute neurological disorders lasting at least for 24 hours. It reflects the focal involvement of central nervous system induced by blood circulation disorders in brain. This study was designed to study D-Dimer and FDP serum levels in ischemic brain stroke patients with and without malignancy. Method of study: This is a randomized clinical trial in the form of a case-control study. The population of study consists of all cases admitted in the neurology department of Imam-Khomeini Hospital in Urmia who included in the study via randomized allocation after obtaining their consent. Cases with underlying malignancy were grouped in case group and those with no malignancy were grouped in control group. Results: In this study, 60 and 120 cases were studied in the case and control groups, respectively. There was a significant difference in mean D-Dimer (P=0.01), mean FDP (P=0.02), mean ESR (P=0.01) and mean CRP (P=0.01) between case and control groups. Lung cancer was the most prevalent cancer (31.7%) in the case group. In addition, diabetes mellitus, hyperlipidemia and hypertension risk factors were reported in the case group with a frequency of 28.3%, 33.3% and 30%, respectively. Conclusion: In patients with ischemic stroke and malignancy, the serum levels of D-dimer and ESR was elevated and risk factors such as DM, HLP, and HTN had a high rate in these patients, so in patients with cancer, occurrence of cerebral ischemia is higher compared to patients without malignancy. So knowing mechanisms, type and stage of cancer is critical for survival of these patients.Keywords: Diabetes mellitus, D-Dimer, ESR, Hyperlipidemia, Hypertension, Ischemic stroke.